The effect of sawdust on compaction properties of peat soil - Noor Elyya, Mohd (2013)
The improvement of soil is the one of the most importance criteria that should be considered for construction on soft soil. It is well known that improvement of the ground will affect the stability of the structure above it and there are many types of soil to deal with, depending on the area, its location; its surroundings and various other factors. This thesis is deals with the effect of sawdust on the compaction properties of peat soil. As we all known, in the civil engineering work, the construction of the roads , bridge, canals, dam and building is very important to make sure the base layer of these is strong enough to support the load from the superstructure. Thus, the proper soil analysis is very important so as to check the soil strength and the moisture content of soil and also to make sure the structure is stay safe and can endure from sinking. Compaction test is used on this research to determine the optimum moisture content of the peat soil and sawdust in various mixes, to determine the maximum dry density of peats soil and sawdust for various mixes and to define the optimum moisture mix for the peat soil sawdust which gives the maximum compaction properties performance. The acquired results indicates that when the amount of sawdust is increase, the maximum dry density is decrease and the optimum moisture content was increase. Therefore, the results concluded that the addition of sawdust has an influence in increasing physical strength of natural peat soil.